2006
DOI: 10.1080/01460860600846941
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Low Birth Weight to Blood Pressure, Cortisol Levels, and Reactivity in African American Adolescents: A Pilot Study

Abstract: Epidemiological studies show a relationship between low birth weight (LBW) and adult cardiovascular disease. Blood pressure and cortisol hyper-responsiveness during physiologic stress may function as biological markers for hypertension. The purpose of this study was to explore the relationship of blood pressure and cortisol levels with induced physiologic stress to LBW. Forty-eight adolescents, 14 to 16 years old, were tested for blood pressure and cortisol levels at rest and in response to a physiological str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Exaggerated neuroendocrine and vasoconstrictive responses have been shown to predict the development of hypertension in adults. 4 Therefore, the exaggerated EPR response, in our study, may function as a marker for the pathophysiologic phases of hypertension.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Exaggerated neuroendocrine and vasoconstrictive responses have been shown to predict the development of hypertension in adults. 4 Therefore, the exaggerated EPR response, in our study, may function as a marker for the pathophysiologic phases of hypertension.…”
Section: Discussionmentioning
confidence: 57%
“… 3 Previous studies have also shown that exaggerated vasoconstrictive and neuroendocrine responses are associated with development of hypertension in adults and may function as markers for preclinical or pathophysiologic phases of hypertension. 4 , 5 LBW is associated with an increased sympathetic nerve activity and therefore predisposing LBW individuals to development of hypertension in adulthood. 6 8 …”
Section: Introductionmentioning
confidence: 99%
“…Another factor contributing to our findings could have been “white coat” effect during the measurement of blood pressure, as the children would not have been familiar with these measurements. Other studies have reported higher vascular reactivity to stressors in adulthood in those born small or after intrauterine growth retardation (Feldt et al, ; McCormick Covelli, ; Painter et al, ). As the physiological toleration of stress may also be considered a component of homeostasis, this could still be considered under the umbrella of a broad capacity‐load model, in which greater nutritional investment in early life promotes multiple components of metabolic capacity.…”
Section: Discussionmentioning
confidence: 87%